Subliminal Emotional Words Impact Syntactic Processing: Evidence from Performance and Event-Related Brain Potentials - Jiménez-Ortega, Laura; Espuny, Javier; de Tejada, Pilar Herreros; Vargas-Rivero, Carolina; Martín-Loeches, Manuel (Frontiers in Human Neuroscience, 2017)
Recent studies demonstrate that syntactic processing can be affected by emotional information and that emotional subliminal information can also affect cognitive processes. In this study, we explore whether unconscious emotional information may also impact syntactic processing. In an Event-Related brain Potential (ERP) study, positive, neutral, and negative subliminal adjectives were inserted within neutral sentences, just before the presentation of the supraliminal adjective, that could be either correct (50%) or contain a morphosyntactic violation. Larger error rates were observed for incorrect sentences in comparison to correct ones, at variance with most studies using supraliminal information. Strikingly, emotional adjectives affected syntactic conscious processing of sentences containing morphosyntactic anomalies. Neutral condition elicited left anterior negativity followed by a P600 component. However, a lack of anterior negativity and an early P600 onset for the negative condition was found, probably as a result of the negative subliminal correct adjective capturing early syntactic resources. Positive masked adjectives in turn prompted an N400 component to morphosyntactic violations, probably reflecting the induction of an heuristic processing mode involving the access to lexico-semantic information to solve agreement anomalies. Our results add to recent evidence on the impact of emotional information on syntactic processing, while showing that this can occur even when the reader is unaware of the emotional stimuli.